Ability-Tracking, Instructional Time, and Better Pedagogy: The Effect of Double-Dose Algebra on Student Achievement - Cortes, Kalena E.; Goodman, Joshua S. (American Economic Review, 2014)
This paper provides new evidence on tracking by studying an innovative curriculum implemented by Chicago Public Schools (CPS). In 2003, CPS enacted a double-dose algebra policy requiring 9th grade students with 8th grade math scores below the national median to take two periods of algebra instead of one. This policy led schools to sort students into algebra classes by math ability, so that tracking increased in all algebra classes. We show that double-dosed students are exposed to a much lower-skilled group of peers in their algebra classes but nonetheless benefit substantially from the additional instructional time and improved pedagogy.